Innovation and Validation of Relative Permeability Experimental Tools Using Metal Materials as a Medium for High School Physics Education - Ernidawati Ernidawati; Mitri Irianti; Zuhdi Ma’ruf; Idris Idris; Wilda Novianti; Abdul Hamid Sinaga; Rahmi Hidayah; Dhuha Fatihul Burhan (Postgraduate, University of Mataram, 2025)
This research is motivated by the limitations of physics learning media in high schools, especially in magnetism materials, which are abstract and difficult to understand without the support of appropriate experimental tools. This condition hinders students' ability to relate theory to real phenomena. This research aims to develop and test the feasibility of a relative permeability experiment tool for metal materials as a high school physics learning medium. This tool is designed to help students understand the concept of magnetism, especially the relationship between the number of turns, voltage, current strength, magnetic induction, and relative permeability in various types of metals. The research method used is research and development (R&D). The test results show that steel has an average relative permeability value (μr) of 3.9, which indicates strong ferromagnetic properties, while iron has an μr of around 1.4 with moderate ferromagnetic properties. Aluminum with an average μr of 1.0 and brass, with an average μr of 0.7 are classified as non-ferromagnetic. Thus, this test tool can clearly distinguish ferromagnetic and non-ferromagnetic materials based on their relative permeability values. Validation was conducted by three experts, with an average value of 3.77, which is considered very high. Furthermore, a practicality test involving 16 high school physics teachers showed a very high practicality category. Based on these results, it can be concluded that the developed relative permeability experiment tool is valid, practical, and suitable for use as a physics learning medium to improve students' understanding of the concept of magnetism